Construction Strategy for an Internal Amplification Control for Real-Time Diagnostic Assays Using Nucleic Acid Sequence-Based Amplification: Development and Clinical Application - Rodríguez-Lázaro, David (American Society for Microbiology, 2004)
An important analytical control in molecular amplification-based methods is an internal amplification control (IAC), which should be included in each reaction mixture. An IAC is a nontarget nucleic acid sequence which is coamplified simultaneously with the target sequence. With negative results for the target nucleic acid, the absence of an IAC signal indicates that amplification has failed. A general strategy for the construction of an IAC for inclusion in molecular beacon-based real-time nucleic acid sequence-based amplification (NASBA) assays is presented. Construction proceeds in two phases. In the first phase, a double-stranded DNA molecule that contains nontarget sequences flanked by target sequences complementary to the NASBA primers is produced. At the 5′ end of this DNA molecule is a T7 RNA polymerase binding sequence. In the second phase of construction, RNA transcripts are produced from the DNA by T7 RNA polymerase. This RNA is the IAC; it is amplified by the target NASBA primers and is detected by a molecular beacon probe complementary to the internal nontarget sequences. As a practical example, an IAC for use in an assay for the detection of Mycobacterium avium subsp. paratuberculosis is described, its incorporation and optimization within the assay are detailed, and its application to spiked and natural clinical samples is shown to illustrate the correct interpretation of the diagnostic results.